Cold tolerance of two Antarctic terrestrial arthropods - Block, William; Young, Stephen R; Conradi-Larsen, Else-Margrete; Sømme, Lauritz (Experientia, 1978)
Two Antarctic arthropods,Alaskozetes antarcticus (Acari) andCryptopygus antarcticus (Collembola) possess the ability to supercool to −30°C, but the realisation of this potential is dependent on starvation. The mite contains glycerol in a concentration of about 1% fresh weight.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; virvelløse dyr

Age relationships of Mesozoic basalt lava and dykes in Vestfjella, Dronning Maud Land, Antarctica - Furnes, Harald; Mitchell, John G (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geokjemi; geologi; petrografi; vulkaner

Glaciological studies by Landsat imaginery of perimeter of Dronning Maud Land, Antarctica - Orheim, Olav (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; NARE ekspedisjoner; geologi; glasiologi; havis; isbreer

Results from Norwegian Antarctic research 1974-1977 - Polarinstitutt, Norsk (1978)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner

Snow accumulation and snow stratigraphy on Riiser-Larsenisen, Dronning Maud Land, Antarctica - Repp, Kjell (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geologi; glasiologi; isshelf; snø; stratigrafi